2015
DOI: 10.1590/0102-311x00166714
|View full text |Cite
|
Sign up to set email alerts
|

The place where you live and self-rated health in a large urban area

Abstract: The place where you live and self-rated health in a large urban area O lugar onde se vive e a autoavaliação da saúde em um grande centro urbano El lugar donde se vive y la autopercepción de la salud en un gran centro urbano

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
10

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 34 publications
2
18
0
10
Order By: Relevance
“…In this study, “citizens’ services,” a factor related to women’s general health, refers to the respondents’ perceived access to a family health center, as well as the extent of opportunities for community participation in plans and events within the neighborhood. These findings are consistent with two studies from Brazil demonstrating links between the quality of public services and better self-reported health [ 5 , 16 ]. Prioritizing the early availability of good citizens’ services in new neighborhoods may help deliver better self-reported general health for their residents.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, “citizens’ services,” a factor related to women’s general health, refers to the respondents’ perceived access to a family health center, as well as the extent of opportunities for community participation in plans and events within the neighborhood. These findings are consistent with two studies from Brazil demonstrating links between the quality of public services and better self-reported health [ 5 , 16 ]. Prioritizing the early availability of good citizens’ services in new neighborhoods may help deliver better self-reported general health for their residents.…”
Section: Discussionsupporting
confidence: 92%
“…Previous international studies have identified a wide range of neighborhood environmental factors that are associated with self-reported general health: neighborhood problems [ 17 ], sociability [ 18 ], neighborhood amenities [ 19 ], the physical quality of residential areas [ 20 ], fewer physical and social disorders [ 5 ], the neighborhood’s physical environment [ 4 ], social cohesion and a general feeling of safety [ 21 ], and social safety [ 22 ]. While our results, which focus on middle-aged women in urban neighborhoods, did not identify some of these relationships, each of these factors has a potential impact on self-reported health in different contexts and populations in Mongolia and should be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex is one of several well-established independent determinants of SRH. In fact, women usually report worse SRH than men, especially at younger ages [ 12 ]. Consistently, a study conducted in Belo Horizonte, Minas Gerais, Brazil in 2013 evaluated the relationship between the physical and social environment and SRH in 4048 adults 18 years and older from a large urban center and showed that women were 38.0% more likely than men to rate their health as poor [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…We know that public health policies should incorporate interventions that address urban physical and social environments in addition to policies focused on individuals (Rodrigues et al 2015). Focusing only on treatment interventions for individuals in cities is bound to fail because individuals will be forced to go back into the urban living and working conditions that may have made them sick in the first place (Corburn 2015).…”
Section: Disclosure Statementmentioning
confidence: 99%